2007
DOI: 10.1007/s00894-007-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the differences in the folding mechanisms of c-type lysozymes based on contact maps constructed with interresidue average distances

Abstract: A method for analyzing differences in the folding mechanisms of proteins in the same family is presented. Using only information from the amino acid sequences, contact maps derived from the interresidue average distances are employed. These maps, referred to as average distance maps (ADM), are applied to the folding of c-type lysozymes. The results reveal that the ADMs of these lysozymes reflect the differences in the detailed folding mechanisms. Further possible applications of the present method are also dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…In this study, in order to detect the property of partial peptide sequences, which tend to form compact structures, we use the ADM method. The ADM method predicts the possible compact regions in a protein from its amino acid sequence and predicted regions correspond well to structural domains [5,6,25], and experimentally observed folding regions including highly protected regions measured by NMR during folding [26,27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…In this study, in order to detect the property of partial peptide sequences, which tend to form compact structures, we use the ADM method. The ADM method predicts the possible compact regions in a protein from its amino acid sequence and predicted regions correspond well to structural domains [5,6,25], and experimentally observed folding regions including highly protected regions measured by NMR during folding [26,27,28]. …”
Section: Resultsmentioning
confidence: 99%
“…5(b) as a measure of compactness of the region E-F. For several proteins, we have confirmed that such a compact region on ADM can also be regarded as a folding unit in the sequence of a protein (Ichimaru & Kikuchi, 2003;Nakajima et. al, 2005;Nakajima & Kikuchi, 2007;Kikuchi, 2011).…”
Section: Construction Of a Predicted Contact Mapmentioning
confidence: 99%
“…This part grows to the final native structure. -Sandwich proteins such as titin, azurin (Ishizuka & Kikuchi, 2011) and so on, proteins in the c-type lysozyme fold (Nakajima & Kikuchi, 2007), sandwich proteins (Matsuoka & Kikuchi, unpublished) such as ribosomal protein S6, and so on may belong to this category. In this case, the ADM for a protein tends to predict the location of folding cores which should aggregate into the larger hydrophobic core.…”
Section: A Protein Containing Long Range Interactions Along Its Sequencementioning
confidence: 99%
“…In a series of studies, we have applied an analysis method based on inter-residue average distance statistics to predict the location of structural domains [6], compact regions during the folding of fatty acid binding proteins [7], globin fold proteins [8], c-type lysozyme proteins [9] and β-sandwich proteins [10]. This technique has also been used to analyze the GA and GB proteins' related sequences, which are 60% identical to each other, and the sequential properties that result in the exhibition of either structure have been determined [11].…”
Section: Introductionmentioning
confidence: 99%